Ayurveda management of Ashmari w.s.r. Renal Calculi: A Single Case Study. - Makwana, Dhaval; Panja, Asit; Chudasama, Hardik; Engineer, Priti (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Urolithiasis, the third most prevalent condition affecting the Mutravaha srotas, has a significant recurrence rate and adversely affects the quality of life. The current study aims to investigate the collective impact of Ayurvedic medication, dietary modifications, and lifestyle adjustments on the fragmentation and elimination of calculi. Material & Methods: A 35-year-old male patient presenting with symptoms of abdominal pain, nausea, vomiting, and painful urination was diagnosed with ashmari based on clinical manifestations and investigative findings. An abdominal ultrasound scan revealed an elongated calculus measuring approximately 9.6 mm in the lower ureter of the right kidney, accompanied by proximal hydroureteronephrosis. The patient was administered the two Chandraprabha Vati along with Tranpanchmoola Kashayam (40 ml) twice daily before meals. Additionally, after a meal, two Gokshuradi Guggulu tablet crushed with Punarnavashtaka Kashayam were administered twice daily with water for five weeks. Results: The study aims to assess the impact of the prescribed Ayurvedic treatment regimen on the fragmentation and elimination of the calculi. Discussion: The study will contribute to understanding the efficacy of Ayurvedic medication, dietary modifications, and lifestyle adjustments in managing urolithiasis. Conclusion: The collective impact of Ayurvedic medication, dietary modifications, and lifestyle adjustments in the treatment of urolithiasis will be evaluated in this study. The results will shed light on the effectiveness of this integrative approach, potentially improving patient outcomes and quality of life.